1992
DOI: 10.1128/jb.174.21.6896-6903.1992
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, expression, and characterization of the Micromonospora viridifaciens neuraminidase gene in Streptomyces lividans

Abstract: We have cloned the Micromonospora viridifaciens neuraminidase (EC 3.2.1.18) gene (nedA) in Streptomyces fividans. This was accomplished by using the vector pU7O2 and BgM-BclI libraries of M. viridifaciens chromosomal inserts created in S. fividans. The libraries were screened for the expression of neuraminidase by monitoring the cleavage of the fluorogenic neuraminidase substrate 2'-(4-methylumbelliferyl)-a-D-N-acetylneuraminic acid. Positive clones (BG6, BG7, BC4, and BC8) contained the identical 2-kb BclI-Bg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
19
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 32 publications
5
19
0
Order By: Relevance
“…The 107-kDa S. pneumoniae NanA is observed as an enzymatically active 86-kDa species following purification (32). The size of the M. viridifaciens NedA protein varies between 41 and 68 kDa depending on the culture conditions (45). Indeed, upon prolonged storage at 4°C, His-NanH converted to a species of 62 kDa, with no loss of specific activity (data not shown).…”
Section: Discussionmentioning
confidence: 95%
“…The 107-kDa S. pneumoniae NanA is observed as an enzymatically active 86-kDa species following purification (32). The size of the M. viridifaciens NedA protein varies between 41 and 68 kDa depending on the culture conditions (45). Indeed, upon prolonged storage at 4°C, His-NanH converted to a species of 62 kDa, with no loss of specific activity (data not shown).…”
Section: Discussionmentioning
confidence: 95%
“…2). The sequence (5Ј-TTGCCA-18 bp-TAACGT-3Ј) resembles the E. coli consensus promoter sequence (5Ј-TTGACA-17 bp-TATAAT-3Ј) (20). A long inverted repeat sequence, which may act as a transcription terminator, was observed downstream of the termination codon of the aphA gene (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, in Clostridium perfringens, the nanH gene is located near a phage attachment site on the chromosome and has a GjC content of 31n9 mol % compared to the chromosomal DNA GjC content of 24-27 mol % (Canard & Cole, 1989). In M. viridifaciens it has been observed that a region flanking the nanH gene shows significant homology to a transposase (Sakurada et al, 1992).…”
Section: Discussionmentioning
confidence: 99%